PREEMPTIVE CADAVERIC KIDNEY TRANSPLANTATION - T. I. Shraer; A. A. Salmayer; T. A. Piminova; Y. L. Reznik; Ju. B. Glebova; O. V. Lucenko; L. D. Chesnokova; N. K. Galcovsky (Вестник трансплантологии и искусственных органов)
An article presents the results of cadaveric kidney transplantation (KT) in patients with end-stage of renal disease (ESRD) before initiation of hemodialysis (n = 20) and in patients after prior hemodialysis (n = 33). Survival of the recipients and transplants in 3 years period after preemptive KT is 90 and 70% respectively, and 90,8 and 60,6% – in patients after prior hemodialysis (р < 0,05). A disturbance frequency of the lipid profile, phosphorus and calcium homeostasis as well as the level of the arterial hypertension and the number of hypotensive drugs were assessed in recipients before hemodialysis and after prior hemodialysis in 3 years period after KT. The received data showed an advantage of preemptive KT compared to KT after prior hemodialysis.